2015
DOI: 10.1038/jhg.2015.23
|View full text |Cite
|
Sign up to set email alerts
|

Japan PGx Data Science Consortium Database: SNPs and HLA genotype data from 2994 Japanese healthy individuals for pharmacogenomics studies

Abstract: Japan Pharmacogenomics Data Science Consortium (JPDSC) has assembled a database for conducting pharmacogenomics (PGx) studies in Japanese subjects. The database contains the genotypes of 2.5 million single-nucleotide polymorphisms (SNPs) and 5 human leukocyte antigen loci from 2994 Japanese healthy volunteers, as well as 121 kinds of clinical information, including self-reports, physiological data, hematological data and biochemical data. In this article, the reliability of our data was evaluated by principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The Japan Society of Human Genetics, Japanese Society of Clinical Pharmacology and Therapeutics, and Japanese Committee for Clinical Laboratory Standards subsequently published clinical pharmacogenetic guidelines in 2010 [23]. Moreover, the Japan Pharmacogenomics Data Science Consortium was established in 2009 by six pharmaceutical companies (Astellas, Daiichi Sankyo, Mitsubishi Tanabe, Otsuka, Taisho, and Takeda) with the aim of supporting pharmacogenomic discovery in Japan during drug development and post-market [24]. Consistent with these efforts, 81.0% of the general Japanese public previously reported a positive attitude towards pharmacogenetics research [25].…”
Section: Discussionmentioning
confidence: 99%
“…The Japan Society of Human Genetics, Japanese Society of Clinical Pharmacology and Therapeutics, and Japanese Committee for Clinical Laboratory Standards subsequently published clinical pharmacogenetic guidelines in 2010 [23]. Moreover, the Japan Pharmacogenomics Data Science Consortium was established in 2009 by six pharmaceutical companies (Astellas, Daiichi Sankyo, Mitsubishi Tanabe, Otsuka, Taisho, and Takeda) with the aim of supporting pharmacogenomic discovery in Japan during drug development and post-market [24]. Consistent with these efforts, 81.0% of the general Japanese public previously reported a positive attitude towards pharmacogenetics research [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CYP2C9*3 carrier status would be sufficient to decrease the probability of adverse reactions associated with phenytoin in the Japanese population. The HLA‐B*15:02 frequency in the Japanese population was reported to be 0.0002–0.001; thus, the clinical utility of the allele in Japanese is quite low . Conversely, the HLA‐B*51:01 allele frequencies in Japanese was reported to be 0.077–0.083 .…”
Section: Discussionmentioning
confidence: 99%
“…The Clinical Pharmacogenetics Implementation Consortium (CPIC) and the Royal Dutch Association for the Advancement of Pharmacy‐Pharmacogenetics Working Group (DPWG) are well known for clinical support provision . However, these guidelines have not been utilized in clinical practice in Japan, given the lack of evidence of the associations with CYP2C9 and extremely low HLA‐B*15:02 frequency in its population . Recently, Su et al reported the associations of phenytoin‐induced hypersensitivity with CYP2C9*3 and HLA‐B alleles in some East Asian populations; however, no HLA‐B alleles showed significant associations in the Japanese population, specifically.…”
mentioning
confidence: 99%
“…RA patients fulfilled the 1987 American College of Rheumatology criteria for RA [ 24 ] or the 2010 Rheumatoid Arthritis Classification Criteria [ 25 ]. Four hundred thirteen Japanese healthy controls (mean age ± SD, 39.3 ± 11.0 years, vs. ACPA(+)RA: P = 6.50X10 -130 , vs. ACPA(-)RA, P = 5.51X10 -71 , 61 male [14.8%], vs. ACPA(+)RA: P = 0.0792, vs. ACPA(-)RA, P = 0.2195) were recruited at Kanazawa University, Sagamihara National Hospital, and Teikyo University [ 26 ] or by the Pharma SNP Consortium (Tokyo, Japan) [ 27 , 28 ]. Rheumatoid factor and ACPA were measured by N-latex RF kit (Siemens Healthcare Diagnostics, München, Germany) or Mesacup-2 test CCP (Medical & Biological Laboratories, Nagoya, Japan), respectively.…”
Section: Methodsmentioning
confidence: 99%